Precuneus Structure Changes in Amnestic Mild Cognitive Impairment. (February 2017) - Haussmann, Robert; Werner, Annett; Gruschwitz, Antonia; Osterrath, Antje; Lange, Jan; Donix, Katharina L.; Linn, Jennifer; Donix, Markus
Patients with amnestic mild cognitive impairment (aMCI) are at risk for developing Alzheimer's disease. Due to their prominent memory impairment, structural magnetic resonance imaging (MRI) often focuses on the hippocampal region. However, recent positron-emission tomography data suggest that within a network of frontal and temporal changes, patients with aMCI show metabolic alterations in the precuneus, a key region for higher cognitive functions. Using high-resolution MRI and whole-brain cortical thickness analyses in 28 patients with aMCI and 25 healthy individuals, we wanted to investigate whether structural changes in the precuneus would be associated with cortical thickness reductions in frontal and temporal brain regions in patients with aMCI. In contrast to healthy people, patients with aMCI showed an association of cortical thinning in the precuneus with predominantly left-hemispheric thickness reductions in medial temporal and frontal cortices. Our data highlight structural neuronal network characteristics among patients with aMCI.